Peningkatan Gelombang Elektromagnetik Menurunkan Laju Perkecambahan Padi Beras Merah Cenana Jatiluwih (Oryza Sativa Var Barac Cenana) - Gede Viqtor Arya Nugraha; I Made Anom S Wijaya; I Wayan Widia (Jurnal BETA (Biosistem dan Teknik Pertanian), 2018)
This study aims to find out the modeling of electromagnetic fields against local rice varieties and to determine the electromagnetic field and the proper immersion time to produce the best rice germination. The experimental experiment used is a factorial circuit consisting of two factors. The first factor is the strength of the electromagnetic field of 0 mT, 2 mT, 3 mT and 4 mT, while the second factor is the duration of immersion consisting of 48, 64, and 96 hours. The data obtained were analyzed by verbal examination, then continued with duncan test if treatment had real effect. The results showed that the stronger electromagnetic exposure with certain voltage resulted in a decrease in the percentage of seed germination of local varieties of rice while for the immersion treatment, the longer the seed immersion resulted in increased percentage of germination of local varieties of rice. The best germination was produced at exposure of 2 mT vol tage electromagnetic field with 96 hours of immersion time for red rice varieties.